PELATIHAN PEMANFAATAN LIMBAH TEMBAKAU SEBAGAI BAHAN PEMBUATAN BIOPESTISIDA NABATI - Sumedi P Nugraha (UII, 2015)
Dusun Kajor Dhuwur is a one of Dusun that located in Lencoh Village, DistrictSelo, Boyolali, Central Java Province. Mostly the residents in Dusun Kajor Dhuwur are afarmers. Although the majority are worked as a farmer. One of plans that they grown isTobacco. More than half of farms planted tobacco. But the use of tobacco is still notmaximal because the residents only sell the raw tobacco. One of the potential that neetto be developed from tobacco is botanical pesticides which is good for for vegetablesand fruits. Part of tobacco that can used as pesticides are the leaf and trunk also the leafthat has been fermented. Tobacco is a plant that has high economic value so for thethrifty, the tobacco that has low quality or has been damaged can be used as materialsfor making botanical pesticides. Beside that, it can increase the economic value of thelow quality tobacco. To maximizing the tobacco products of the residents Dusun Kajor Dhuwur, thetraining to making botanical pesticides from the waste of tobacco is needed for theresidents. Beside that wit h making the botanical pesticides can help the resident ineconomics. Pesticides can increase the values of the waste tobacco or the low qualitytobacco became higher. In the training, will be explain the other benefits from tobaccoas the material of cigarette. The aims of the program is to make the residents can usedthe products as a material for botanical pesticides. The result that got from the training program are the residents of Dusun KajorDhuwur knows the advantages and the disadvantages from botanical pesticides and theresidents can utilizing the low quality tobacco.